Comparison of color light-emitting diode corneal topographer and dual rotating Scheimpflug-placido topographer - Lee, Jae Hyuck; Knorz, Michael C.; Auffarth, Gerd U. (Journal of ophthalmology, 2018)
Purpose: To compare measurements of anterior and posterior keratometric values, using a color light-emitting diode corneal topographer and a dual rotating Scheimpflug-Placido topographer. Methods: Anterior and posterior corneal index measurements were performed using a color light-emitting diode corneal topographer (Cassini) and a dual rotating Scheimpflug-Placido topographer (Galilei G4) and then compared. The paired t-test, intraclass correlation coefficients (ICCs), and Bland-Altman plots were used to evaluate the agreement between measurements. Results: Sixty postrefractive surgery eyes and 60 normal eyes were evaluated. Both the color light-emitting diode corneal topographer and the dual rotating Scheimpflug-Placido topographer provided highly repeatable corneal measurements (ICC > 0.969). The agreement levels between the 2 devices for anterior corneal power, astigmatism magnitude, and J0 and J45 values were ICC > 0.906 for the total group. However, the ICC values for posterior corneal power, astigmatism magnitude, and J0 and J45 values were lower than 0.681 for the total group. Conclusions: The anterior keratometric values obtained by the color light-emitting diode corneal topographer and the dual rotating Scheimpflug-Placido topographer showed high agreement levels, but the posterior keratometric values showed lower agreement levels.
Gesehen am 25.02.2020